Synthesis, Cytotoxic Activity (MTT, Caspase 8,9) Assay and Molecular Docking of Four New Hybrids (Curcumin –Ether Linker- 1,3,4- Oxadiazole ) Compounds as Possible Anti-Cancer - Khuder, Huda Yassien; Hameed, Ayad Saadi; Hassan, Firas Abdulla (Journal of Science in Medicine and Life, 2024)
Four novel hybrids (curcumin – 1,3,4- Oxadiazole) compounds ,namely 1,7 – bis [3- methyloxy ,4-(-(5-aryl -1,3,4- Oxadiazole -2- methyloxy -1- yl ) phenyl ] hepta 1,6- 3,5 dione [H7,-H10] were synthesized and the structures of all the synthesized compounds were characterized using ( FT-IR , 1H-NMR and Mass spectroscopy) and analysis of the spectral data obtained improve the final structure of compounds synthesized , and also these spectral data indicated the successful combination of curcumin and 1,3,4 Oxadiazole through ether linkage.Curcumin and hybrid curcumin [H8] compounds were tested for in vitro cytotoxic activities against one human cancer cell line named (SK-OV-3)as well as a normal cell line(HdFn).( MTT, Caspases 8,9 ) assays which are used to measure cellular metabolic activity, Cytotoxicity test result , showed that curcumin and compound[H8] has concentration dependent anti proliferative effect on SK-OV-3 cell IC50 for curcumin = 149.4μg/ml IC50 for [H8] = 81.30μg/ml,Curcumin and [H8] compounds are significantly reduced the viability of SK-OV-3 cell , the percentage of dead of early apoptotic and late apoptotic cell were detected to be Curcumin (21%, 61%) at 400 μg/ml on HdFn , SK-OV-3 cell. (,16% (49% at 200 μg/ml on HdFn , SK-OV-3 cell respectively[ H8] (27%, 69%) at 400 μg/ml on HdFn , SK-OV-3 cell respectively at 200 μg/ml on HdFn , SK-OV-3 cell respectively (61%,15%). The Molecular docking study was conducted to determine the binding interaction of 1,3,4-oxadiazole , curcumin and the hybrid (curcumin -1,3,4- oxadiazole)compounds with two anti – apoptotic proteins ,namely β-cell lymphoma (BCL-2) and β-cell lymphoma – extra-large (BCL-x1). The binding affinity , the presence of H- bonds between synthesized compounds and target proteins were also explained ,and the result obtained showed that compounds [H8] has the highest binding affinities of (-9.2 and -11.3)Kcal/mol , with (BCL-2 and BCL-xl) proteins The combination of the docking studies and cytotoxic evaluation of curcumin and [H8] showed that these compounds lower SK-OV-3 cell viability , increases pro apoptotic proteins, and decreases BCL-2 and BCL-Xl level therapy inhibiting SK-OV-3 tumor growth , these finding encourage us to development of anew synthetic strategy for cancer treatment. The final result indicted that compound [H8] was potential as an anti-ovarian cancer and we need further studied for investigating its mechanism effect and in (vivo) preclinical studies using an animal model.